PENGARUH FASILITAS KERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA DAN KINERJA PEGAWAI RUMAH SAKIT DAERAH DR. H. SOEMARNO SOSROATMODJO TANJUNG SELOR - Julfitri Harjuma Andayani; Ana Sriekaningsih; Tri Darmayanti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
This study aims to determine the effect and analyze the effect of work facilities and compensation on work motivation and employee performance at the Regional Hospital Dr. H. Soemarno Sosroatmodjo Tanjung Selor. This type of quantitative research is descriptive explanatory. The total population is 400 people and the sample is 80 people. Collecting data by distributing questionnaires and continued in the analysis with path analysis. The results of hypothesis testing are proven that work facilities have an effect on employee work motivation, this is indicated by a significance value smaller than 0.05 and the first hypothesis is accepted. Compensation shows an effect on employee work motivation, this is indicated by a significance value smaller than 0.05 and the second hypothesis is accepted. Work facilities have a direct effect on employee performance, showing that work facilities have a direct significant effect on performance. This means that every increase in work facilities will improve employee performance in carrying out the tasks for which they are responsible. Compensation directly affects employee performance shows that compensation has a direct significant effect on performance. This means that any increase in compensation will directly improve employee performance in carrying out their duties. Work motivation has a significant effect on employee performance, this indicates that any increase in work motivation that has existed so far has a significant impact on employee performance. The direct influence between work facilities and compensation, either partially or simultaneously on employee performance, is greater than the indirect effect, so that the direct effect is more dominant than the indirect effect. Work motivation in this study does not fully partially mediate the effect of work facilities and compensation on employee performance. Likewise, work motivation in this study does not fully partially mediate the effect of work facilities and compensation on employee performance.